Pengaruh Konten “Why” dalam Saluran Youtube Tretan Universe terhadap Mahasiswa di Kota Bandung - Dimas Fitrianto Surya; Arba'iyah (UNISBA Press, 2022)
Abstract. In today's digital era, the audience's need for messages and information is very high. The mass media in the form of electronic and digital are competing to present messages that can meet the need for these messages. Youtube is an online and the main purpose of this site is as a medium for searching, viewing and sharing original videos to and from all corners of the world via a web. One of them is the “WHY” content on the Tretan Universe Youtube channel. A content that contains issues of unrest that are currently happening in Indonesia and then reacted by Stand Up Comedian Tretan Muslim. The purpose of this study was to determine the effect of the intensity, message content and attractiveness of “WHY” content with cognitive, affective and conative aspects on the social attitudes of the 2021 students in Bandung City. The research method used in this research is a quantitative descriptive study. The sampling technique used is simple random sampling, with the research subjects being students of the 2021 class in the city of Bandung who are members of the Line Smansa'20 group totaling 80 people. The results showed a correlation coefficient of rs = 0.845. It can be stated that there is a very strong influence between the